ADAPTASI BUDAYA PADA MASYARAKAT KAMPUNG MINAPADI SAMBEREMBE DI KAPANEWON PAKEM KABUPATEN SLEMAN - Namira Alivia; Eko Murdiyanto; Nanik Dara Senjawati (Agrisociabus, 2022)
Abstract: This study aims to (1) examine the management of Samberembe Minapadi Village; and (2) examine the process of adaptation that occur in the Samberembe hamlet community. This research uses a qualitative approach with the type of case study research. The results of this study indicate that (1) the existing management in the Minapadi Samberembe Village includes planning, implementation, monitoring, and evaluation; (2) The people of Kampung Minapadi Samberembe are able to adapt when interacting with visitors so that they can sort out what is good and bad and always apply the values and norms that they have long embraced.Keywords: management; Samberembe Minapadi Village; social interactions; cultural adaptation.